Pleomorphic adenoma of submandibular gland: not so common occurrence - Gajbhiye, Ashok S.; Deshmukh, Mukteshwar N.; Jaipuriya, Parag K.; Jeughale, Kishor B.; Kumar, Abhinav A.; Ghajbhare, Abhijeet P.; Agrawal, Ankur A. (International Surgery Journal, 2018)
Background: The salivary glands tumour are relatively rare, yet they represent a wide variety of both benign and malignant histologic subtypes. Several studies have been conducted on the tumors of the parotid and minor salivary glands, but very few reports in the literature have focused on submandibular gland tumors as they are rare and are usually grouped with other salivary glands. Approximately 70% of the salivary gland tumors affect parotid gland with the submandibular gland being affected in 5-10% of the cases, sublingual gland in 1% and minor glands in 5-15% of the cases. So, we describe a series of 50 patients of pleomorphic adenoma affecting submandibular gland. Methods: The prospective study was conducted at Department of General Surgery, Indira Gandhi Government Medical College, Nagpur between January 2008 to December 2017. Results: Out of the 50 patients, 10 were male and 40 were female. Thus, male to female ratio is 1:4. Most of the 42 (84%) patients presented with painless swelling in submandibular region. Clinically the tumour has the texture of cartilage and has an irregular and bosselated surface observed in all the patients. The size of tumour was 3 to 6 cm in 32 (64%) patients observed in the present study. Fine needle aspiration cytology was performed in all the patients. All patients were managed by surgical excision. Recurrence occurred in a single patient who was managed with radical excision including a neck dissection with postoperative radiotherapy. Conclusions: Submandibular gland pleomorphic adenoma being common benign tumor, occurring commonly between the 3rd and 5th decade of life and presenting as slow growing asymptomatic swelling with female preponderance. The precise surgical excision along with whole submandibular salivary gland and postoperative radical radiotherapy required for recurrence as the accepted mode of management. However, further long-term studies involving submandibular gland have to be carried out to know the pattern of tumor recurrence.